Strategi Pembinaan dan Manajemen Organisasi PMR dalam Membangun Karakter Peserta Didik Ditingkat Mula di SDN 060913 - Nadila Siswanti; Nadila Adha Lubis; Khafifah Rahmawani Siregar; Usiono U (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to assess the development and management strategies of the Youth Red Cross (PMR) organization in developing the character of students at SDN 060913, especially in the values of responsibility, discipline, cooperation, and social concern. The method used is descriptive qualitative, with data obtained through observation and interviews with 26 active PMR students. The findings show that activities such as first aid training, disaster simulations, and social actions effectively increase discipline, sense of responsibility, teamwork, and concern for the surrounding environment of students. Positive behavioral changes are seen in school life and daily activities. The PMR program has proven to be an effective tool for forming character from an early age. Recommendations are given to expand the reach of activities so that the impact is wider and more sustainable.